Physical and mechanical properties of the hair shaft: A review of measurement techniques to verify the efficacy of cosmetic products - Soares, João Pedro Gonçalves de Souza; Cornélio, Melânia Lopes (Seven Editora, 2024)
Hair is a natural fiber made up of keratin, a protein that contains a high concentration of sulfur from the amino acid cystine. The hair structure is made up of three main regions: the cuticle, the cortex and the medulla. The human hair strand has some unique characteristics, such as: mechanical strength, shine, and combability. Several measurement techniques are reported in the literature to measure the mechanical properties of hair with the main purpose of proving the efficacy of cosmetic products. Some of these methods are: optical and electron microscopy, measurement of mechanical resistance through dynamometers, compression tests to measure combability, evaluation of gloss by specular reflection, among others. In this sense, this work includes a literature review of the techniques for measuring the physical and mechanical properties of the hair fiber, which are extremely important methods in the development of new cosmetic products. DOI:https://doi.org/10.56238/sevened2023.006-127